KUGELS AND COLLARDS stories of food, family, and tradition in jewish south carolina. - BARNETT, RACHEL GORDIN (UNIV OF SOUTH CAROLINA PR, 2023)
A poignant-and delicious-compendium of South Carolina Jewish life revealed through food and story Where people go, so goes their food. In Kugels & Collards: Stories of Food, Family, and Tradition in Jewish South Carolina, Rachel Gordin Barnett and Lyssa Kligman Harvey celebrate the unique and diverse food history of Jewish South Carolina. They gather stories and recipes from diverse Jewish sources-Sephardic and Ashkenazi families who have been in the state for hundreds of years, descendants of Holocaust survivors, and more recent immigrants from Russia and Israel-and explore how cherished dishes were influenced by available ingredients and complemented by African American and regional culinary traditions. These stories are a vital part of the South's "Jewish geography" and foodways, stretching across state lines to shape southern culture. On the southern Jewish table, many cultures are savored. Extensively illustrated with original and archival photographs, Kugels & Collards collects includes more than eighty recipes from seventy contributors. Barnett and Harvey draw on family cookbooks and troves of personal recipes and highlight Jewish staples like kreplach dumplings and stuffed cabbage as well as adaptations of southern favorites such as peach cobbler, plus modern fusions like grits and lox casserole, and of course kugels and collards. Kugels & Collards invites readers into family homes, businesses, and community centers to share meals and memories.
Keywords: Jewish cooking.; Cooking, American -- Southern style.; Cuisine juive.; Cuisine américaine du Sud.; COOKING / Regional & Ethnic / Jewish & Kosher; Cooking, American -- Southern style; Jewish cooking; Electronic books.